An energy-based control scheme for optimal power quality management in 12-pulse rectifier integrated distribution systems. (February 2023) - Xu, Da; Bai, Ziyi; Wang, Tao; Wu, Zhibin; Zhang, Ke
Highlights: Power quality management for 12-pulse rectifier is established to improve its voltage and current adaptability. Power quality of distribution systems is managed based on the magnetic potential balance. An energy-based control scheme is proposed to achieve the optimal power quality. Lower dc-link voltage and better power quality can be achieved. Abstract: This paper proposes an energy-based control scheme for optimal power quality management in 12-pulse rectifier integrated distribution systems. In this 12-pulse rectifier integrated distribution system, instead of using a step-down transformer for voltage matching, a back-to-back converter is connected to the taps of star and delta windings on 12-pulse rectifier transformer's secondary side via the coupling LC. Using the magnetic potential balance of harmonics and reactive components between the back-to-back converter and the load side of the 12-pulse rectifier, the power quality of distribution systems can be managed. This topology can improve the voltage and current adaptability of the converter, thereby saving the cost of voltage matching transformer and exploiting the filter converter capacity potential. To ensure global power quality performance, an energy-based control scheme is proposed to improve the power quality management performance by accelerating the energy dissipation of the system. Case studies are performed to verify the effectiveness and superiority of the proposed methodology on low dc-link voltage and power quality.